Potential Multi-Disaster Based on Landform Characteristic in Parangtritis Area - Irwansyah Sukri (Geographica: Science and Education Journal, 2020)
The assessment of potential disasters is a critical sectoral problem. Because hazard can damage and harm to people. The purpose of this research is to identify potential disasters in Parangtritis area. The identification based on the appraisal variables on some of the multi-hazards that may arise and threaten in this area based on the characteristics of the landform such as gisik, fluvio-marin plain, hills, alluvial plains, and others. This study includes exploratory and evaluation research with a qualitative approach. The results showed some potentially catastrophic hazards in the Parangtritis area, including tsunamis, abrasion, landslides, and floods. Each potential risk has a different level of insecurity and location distribution.